2011
DOI: 10.1007/s00262-011-1005-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cancer testis antigens in human BRCA-associated breast cancers: potential targets for immunoprevention?

Abstract: Introduction Novel breast cancer risk-reducing strategies for individuals with germline mutations of the BRCA1 and/or BRCA2 genes are urgently needed. Identification of antigenic targets that are expressed in early cancers, but absent in normal breast epithelium of these high-risk individuals, could provide the basis for the development of effective immunoprophylactic strategies. Cancer testis (CT) antigens are potential candidates because their expression is restricted to tumors, and accumulating data suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
(55 reference statements)
1
16
0
Order By: Relevance
“…A number of studies have previously established the expression of CTAs in breast tumors, and in some cases CTA expression was shown to be associated with hormone-receptor negative breast cancers (41,(43)(44)(45)(46)(47)(48)(49). However, these studies reported mostly on MAGE gene expression rather than protein levels or on the expression of Mage protein families rather than on specific proteins.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have previously established the expression of CTAs in breast tumors, and in some cases CTA expression was shown to be associated with hormone-receptor negative breast cancers (41,(43)(44)(45)(46)(47)(48)(49). However, these studies reported mostly on MAGE gene expression rather than protein levels or on the expression of Mage protein families rather than on specific proteins.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, cancer testis antigens such as MAGE-A3 and NY-ESO-1 are most prevalent in TNBCs, as demonstrated by several groups. 17,18 TILs at diagnosis therefore likely indicate an ongoing antitumor immune response, which can contribute to improved outcomes (as shown for other solid tumors 19,20 ), although underlying mechanisms such as increased response to cytotoxics (suggested by neoadjuvant study 3 ) and/or eradication of micrometastatic disease have not yet been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Curigliano et al [30] More recently, the high expression of CT antigens mapping to chromosome X (CT-X) genes, including MAGE-A, has been correlated with worse survival in a multivariate analysis of 394 TN breast cancers [32]. Furthermore, Adams et al [33] reported a high incidence of CT antigen Table 1. Main criteria for a prophylactic (breast) cancer vaccination Therapeutic breast cancer vaccination against tumor-restricted antigens [3] Viral targets for prophylactic cancer vaccination [52] Self-targets for prophylactic breast cancer vaccination [67] -A sufficient number of immune cells with highly avid recognition of tumor antigens must be generated in vivo.…”
Section: Viral Targets For Prophylactic Cancer Vaccinationmentioning
confidence: 99%
“…Under the selective pressure of vaccine-induced immune response, tumors may downmodulate the antigen resulting in antigen loss variants. Furthermore, since intracellular CT antigens are processed and presented by major histocompatibility complex (MHC) molecules for immune recognition, tumor downmodulation of MHC-I or the peptide-processing machinery could also hamper effective immunoprevention [33].…”
Section: Therapeutic Breast Cancer Vaccination Against Tumor-restrictmentioning
confidence: 99%